2004
DOI: 10.1007/s00213-003-1589-5
|View full text |Cite
|
Sign up to set email alerts
|

Baclofen reverses the reduction in prepulse inhibition of the acoustic startle response induced by dizocilpine, but not by apomorphine

Abstract: These results indicate that GABA(B) receptors are implicated in the neurobiological circuitry accounting for glutamatergic action in sensorimotor gating, and therefore can be proposed as putative new targets in the pharmacological therapy of psychotic disorders. Further studies should be addressed to evaluate more closely the clinical efficacy of baclofen in this respect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
36
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 51 publications
8
36
1
Order By: Relevance
“…Consistent with our findings, it was reported that baclofen reversed the reduction in PPI induced by MK-801, but not by apomorphine (a direct dopamine receptor agonist), in rats (Bortolato et al, 2004), and that baclofen and clozapine, but not haloperidol, improved spontaneous PPI deficit in mice (Bortolato et al, 2007). In addition, a recent study (Wolf et al, 2007) demonstrated that acute and subchronic treatment with clozapine failed to ameliorate PPI deficits in mice.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our findings, it was reported that baclofen reversed the reduction in PPI induced by MK-801, but not by apomorphine (a direct dopamine receptor agonist), in rats (Bortolato et al, 2004), and that baclofen and clozapine, but not haloperidol, improved spontaneous PPI deficit in mice (Bortolato et al, 2007). In addition, a recent study (Wolf et al, 2007) demonstrated that acute and subchronic treatment with clozapine failed to ameliorate PPI deficits in mice.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a marked reduction of GABA B receptors was reported in the hippocampus and prefrontal cortex (Mizukami et al, 2000;Ishikawa et al, 2005). Although the role of GABA B receptors in schizophrenia and related disorders is still poorly understood, recent pharmacologic studies have demonstrated that baclofen, a GABA B receptor agonist, prevents PPI deficits in rodents (Bortolato et al, 2004(Bortolato et al, , 2007.…”
Section: Introductionmentioning
confidence: 99%
“…Startle amplitudes were compared by a three-way ANOVA, with pretreatment and treatment as independent variables and blocks as repeated factors. In keeping with previous findings by our group (Bortolato et al, 2004) Table 2). %PPI analysis, conducted by a second three-way, repeated-measure ANOVA, showed that apomorphine produced a dramatic reduction in PPI, as expected [F(1,80 Topiramate and prepulse inhibition R Frau et al Figure 2, post hoc comparisons revealed that animals treated with TPM + saline exhibited an increased %PPI in comparison with the rats subjected to a double saline injection (po0.01 for each TPM dose, Tukey).…”
Section: Effects Of Tpm Pretreatment Vs Apomorphinesupporting
confidence: 93%
“…As mentioned in the introduction, TPM produces a variety of inhibitory pharmacological and physiological effects relevant to acoustic startle response (ASR), including AMPA receptor antagonism (Gibbs et al, 2000), blockade of voltage-gated Na + channels (Taverna et al, 1999), and particularly GABA activation (White et al, 1997). Assuming that the observed reduction in startle reflex may reflect the GABAergic mechanism of TPM, our data appear to align to previous results from our group, indicating that GABAergic activators determine a dosedependent decrease in startle amplitude (Bortolato et al, 2004). Previous evidence suggests that animals treated with a subchronic administration of TPM exhibit dramatic startle response reductions only after exposure to stressors (Khan and Liberzon, 2004).…”
Section: Effects Of Tpm On Startle Reflexsupporting
confidence: 88%
See 1 more Smart Citation